Phosphorus negative electrode, preparation method thereof and all-solid-state lithium ion battery

By coating the sulfide solid electrolyte on the phosphorus negative electrode active material and coating the metal material, an all-solid lithium-ion battery is prepared, which solves the problem of poor rate performance and cycle performance of existing lithium batteries, and achieves more efficient charging and discharge and longer battery life.

CN119601616APending Publication Date: 2025-03-11GTC-POWER ZHUHAI TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411602827.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The current lithium batteries have poor rate performance and cycle performance, making it difficult to meet the needs of efficient charging and discharge and long life.

Method used

All-solid lithium-ion batteries are prepared by coating the phosphorus negative electrode active material with a solid electrolyte and further coating metal materials if necessary, thereby improving the rate performance and cycling performance of the battery.

Benefits of technology

This technical method significantly improves the rate performance and cycle performance of lithium-ion batteries, can charge and discharge more efficiently, and maintain high battery performance during long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601616A_ABST
    Figure CN119601616A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and particularly discloses a phosphorus negative electrode, a preparation method thereof and an all-solid-state lithium ion battery. Comprising a negative active material and sulfide solid electrolyte, the sulfide solid electrolyte coats the negative active material; the negative electrode active material comprises phosphorus; and the D50 of phosphorus is 20-30 [mu] m. The all-solid-state lithium ion battery is prepared by coating the phosphorus material with the sulfide solid electrolyte, so that the rate capability and the cycle performance of the battery are improved. And the metal material is further coated on the phosphorus material, so that the rate capability and the cycle performance of the battery are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a phosphorus negative electrode and a preparation method thereof, and an all-solid-state lithium-ion battery. Background Art

[0002] Secondary batteries can convert chemical energy into current to provide electrical energy, which is the discharge process; when a corresponding voltage is applied to both ends of the battery, electrical energy can be converted into chemical energy and stored, which is the charging process. Among secondary batteries, lithium secondary batteries have a high energy density, so lithium secondary batteries are widely used as power sources for mobile devices (such as notebook personal computers and portable phones).

[0003] In the use of lithium cobalt oxide (Li 1-x When CoO2) is used as the positive electrode active material, during charging, the following reactions are performed at the positive electrode. The forward direction is the charging process, and the reverse direction is the discharging process; wherein Li 1-x CoO2→Li 1-x CoO2+xLi + +xe - , (0≤x≤1). When phosphorus (P) is used as the negative electrode active material, during charging, the following reaction occurs at the negative electrode. The forward direction is the charging process, and the reverse direction is the discharging process; where P+(3-x)Li + +(3-x)e - →Li (3-x) P, (0≤x≤3). During the battery charging process, phosphorus reacts with lithium to form lithium phosphide, which allows lithium ions to be stored in the negative electrode; during the battery discharging process, lithium cobalt oxide (Li 1-x CoO2) recombine with lithium ions to form lithium cobalt oxide, thus making the battery charge and discharge cycle possible. However, the battery rate performance and cycle performance of the current battery are still poor.

[0004] Therefore, it is necessary to provide a phosphorus negative electrode active material and a preparation method thereof and an all-solid-state lithium ion battery, so as to further improve the rate performance and cycle performance of the battery. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a phosphorus negative electrode and a preparation method thereof and an all-solid-state lithium-ion battery, so as to further improve the rate performance and cycle performance of the battery.

[0006] A first aspect of the present invention provides a phosphorus negative electrode.

[0007] Specifically, it is characterized by comprising a negative electrode active material and a sulfide solid electrolyte;

[0008] The sulfide solid electrolyte coats the negative electrode active material;

[0009] The negative electrode active material includes phosphorus;

[0010] The phosphorus D 50 20~30μm.

[0011] Preferably, the phosphorus D 50 25~30μm.

[0012] Further preferably, the phosphorus D 50 is 26μm.

[0013] Preferably, the sulfide solid electrolyte includes Li2S-P2S5-LiCl, LiI-LiBr-Li3PS4, Li2S-SiS2, Li2S-P2S5, Li2S-P2S3, Li2S-P2S3-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiCl-LiBr-Li3PS4, LiI-Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, LiI-Li2O-Li2S-P2 S5, LiI-Li2S-P2O5, Li2S-P2S5-LiI, Li2S-P2S5-Li2O-LiI, LiI-Li3PO4-P2S5, Li2S-P2S5, Li3PS4, LiI-Li2S-SiS2- P2S5, LiCl-LiBr-Li2S-P2S5, LiCl-LiBr-Li2S-SiS2, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li3PS4-Li4GeS4, Li 3.4 P 0.6 Si 0.4 S4, Li 3.25 P 0.75 Ge 0.25 S4, Li 4-x Ge 1-x P x S4, at least one of (0≤x≤1).

[0014] Preferably, the negative electrode active material further comprises a metal material; the metal material covers the phosphorus.

[0015] Preferably, the metal material includes at least one of indium, tin and antimony.

[0016] Preferably, the D of the sulfide solid electrolyte is 50 0.1~5μm.

[0017] Further preferably, the D of the sulfide solid electrolyte is 50 1~3μm.

[0018] More preferably, the D of the sulfide solid electrolyte is 50 is 3μm.

[0019] Preferably, the proportion of the sulfide solid electrolyte coating the surface of the negative electrode active material is 65-100%.

[0020] Further preferably, the proportion of the sulfide solid electrolyte coating the surface of the negative electrode active material is 68-100%.

[0021] More preferably, the proportion of the sulfide solid electrolyte coating the surface of the negative electrode active material is 68-90%.

[0022] Preferably, the mass ratio of the sulfide solid electrolyte to the negative electrode active material is 1:2-3.

[0023] Further preferably, the mass ratio of the sulfide solid electrolyte to the negative electrode active material is 1:2 to 2.5.

[0024] More preferably, the mass ratio of the sulfide solid electrolyte to the negative electrode active material is 1:2.2-2.5.

[0025] A second aspect of the present invention provides a method for preparing a phosphorus negative electrode.

[0026] Specifically, the following steps are included:

[0027] After phosphorus is pretreated with trace materials, negative electrode active materials are obtained, and then sulfide solid electrolyte is added to perform ball milling mixing, ultrasonic dispersion, heating, and mixing to obtain a phosphorus negative electrode.

[0028] Preferably, the method further comprises the following step: coating the negative electrode active material with a metal material.

[0029] Preferably, the mixing temperature is 45-55° C. and the mixing time is 1-10 min.

[0030] More preferably, the mixing temperature is 50-55° C. and the mixing time is 1-5 min.

[0031] More preferably, the mixing temperature is 50° C. and the mixing time is 5 min.

[0032] Preferably, the trace material includes at least one of a trace material containing vitamin C, a trace material containing sulfur, a trace material containing phosphorus, and a trace material containing fluorine.

[0033] A third aspect of the present invention provides an all-solid-state lithium-ion battery.

[0034] Specifically, the all-solid-state lithium-ion battery includes the phosphorus negative electrode provided in the first aspect.

[0035] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0036] The present invention prepares an all-solid-state lithium-ion battery by coating a phosphorus material with a sulfide solid electrolyte, thereby improving the rate performance and cycle performance of the battery. The phosphorus material is further coated with a metal material, thereby further improving the rate performance and cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 TEM image of phosphorus negative electrode active material. DETAILED DESCRIPTION

[0038] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0039] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0040] Example 1

[0041] A phosphorus negative electrode and a preparation method thereof.

[0042] Phosphorus negative electrode: The negative electrode active material is phosphorus, of which D 50 26μm; the sulfide solid electrolyte is Li2S-P2S5-LiCl particles, and the D 50 The surface thickness of the negative electrode active material is 3 μm; the proportion of the sulfide solid electrolyte covering the negative electrode active material surface is 68%.

[0043] Preparation method:

[0044] 0.5% vitamin C was added to 5% diluted hydrochloric acid, and phosphorus was added and stirred at room temperature for 20 hours. After washing, it was dried by a rotary evaporator to obtain a negative electrode active material.

[0045] Next, 70.0g of the negative electrode active material and 30.0g of Li2S-P2S5-LiCl particles were mixed in a ball mill state, and then further ultrasonically dispersed. The ultrasonically dispersed body was heated at 100°C for 2h. Next, the precursor powder was placed in a dry mixing device, and the temperature was set to 50°C and the speed was set to 2000rpm for mixing for 5min, and then Li2S-P2S5-LiCl particles and polyvinylidene fluoride (PVDF) were added and mixed to obtain a phosphorus negative electrode.

[0046] Example 2

[0047] A phosphorus negative electrode and a preparation method thereof.

[0048] Phosphorus negative electrode: The negative electrode active materials are phosphorus and indium, in which indium is coated with phosphorus, and phosphorus D 50 The thickness of the indium coating layer is 26 μm, and the thickness of the indium coating layer is 200 nm. The sulfide solid electrolyte is Li2S-P2S5-LiCl particles, and the D 50 The surface thickness of the negative electrode active material is 3 μm; the proportion of the sulfide solid electrolyte covering the surface of the negative electrode active material is 86%.

[0049] Preparation method:

[0050] Add 0.5% vitamin C to 5% dilute hydrochloric acid, add phosphorus and stir at room temperature for 20 hours. After washing, use a rotary evaporator to dry to obtain pretreated phosphorus. Then use the chemical vapor deposition method to coat phosphorus with indium. Use trimethyl indium as a precursor, introduce trimethyl indium gas at a pressure of 0.01 Torr, maintain the pressure at 0.5 Torr, and pre-decompose at 200°C. This step can be repeated many times to obtain an indium coating layer with a thickness of 200nm. Further sinter at 500°C for 2 hours at a pressure of 0.01 Torr to remove organic molecules, and through high temperature, obtain a more solid and denser indium surface coating layer to obtain a negative electrode active material.

[0051] Next, 70.0g of the negative electrode active material and 30.0g of Li2S-P2S5-LiCl particles were mixed in a ball mill state, and then further ultrasonically dispersed. The ultrasonically dispersed body was heated at 100°C for 2h. Next, the precursor powder was placed in a dry mixing device, and the temperature was set to 50°C and the speed was set to 2000rpm for mixing for 5min, and then Li2S-P2S5-LiCl particles and polyvinylidene fluoride (PVDF) were added and mixed to obtain a phosphorus negative electrode.

[0052] Example 3

[0053] A phosphorus negative electrode and a preparation method thereof.

[0054] Phosphorus negative electrode: The negative electrode active materials are phosphorus and tin, in which tin coats phosphorus and phosphorus D 50 26 μm, the thickness of the tin coating layer is 200 nm; the sulfide solid electrolyte is Li2S-P2S5-LiCl particles, and the D 50 The surface thickness of the negative electrode active material is 3 μm; the proportion of the sulfide solid electrolyte covering the surface of the negative electrode active material is 87%.

[0055] Preparation method:

[0056] The difference from Example 1 is that trimethyltin is used as a precursor, and the remaining steps are the same as those of Example 1.

[0057] Comparative Example 1

[0058] A graphite negative electrode and a preparation method thereof.

[0059] The difference from Example 1 is that the negative electrode active material is graphite particles, and the D 50 The surface area of ​​the negative electrode active material is 26 μm, and the other materials and preparation methods are the same as those in Example 1; wherein the proportion of the sulfide solid electrolyte coating the surface of the negative electrode active material is 70%.

[0060] Comparative Example 2

[0061] A phosphorus negative electrode and a preparation method thereof.

[0062] The difference from Example 1 is that the negative electrode active material is phosphorus, and the D 50 The surface area of ​​the negative electrode active material is 50 μm, and the other materials and preparation methods are the same as those in Example 1: wherein the proportion of the sulfide solid electrolyte coating the surface of the negative electrode active material is 76%.

[0063] Comparative Example 3

[0064] A phosphorus negative electrode and a preparation method thereof.

[0065] The difference from Example 1 is that the negative electrode active material is phosphorus, and the D 50 The surface area of ​​the negative electrode active material is 12 μm, and the other materials and preparation methods are the same as those in Example 1; wherein the proportion of the sulfide solid electrolyte coating the surface of the negative electrode active material is 61%.

[0066] Comparative Example 4

[0067] A phosphorus negative electrode and a preparation method thereof.

[0068] The difference from Example 1 is that 80.0 g of negative electrode active material and 20.0 g of Li2S-P2S5-LiCl particles are added and mixed, and the remaining materials and preparation methods are the same as those of Example 1. The proportion of sulfide solid electrolyte covering the surface of the negative electrode active material in the prepared phosphorus negative electrode is 62%.

[0069] Comparative Example 5

[0070] A phosphorus negative electrode and a preparation method thereof.

[0071] The difference from Example 1 is that 60.0 g of negative electrode active material and 40.0 g of Li2S-P2S5-LiCl particles are added and mixed, and the remaining materials and preparation methods are the same as those of Example 1. The proportion of sulfide solid electrolyte covering the surface of the negative electrode active material in the prepared phosphorus negative electrode is 84%.

[0072] All-solid-state lithium-ion batteries were manufactured by using the negative electrodes of each embodiment and comparative example:

[0073] positive electrode:

[0074] LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 particles are coated with LiNbO3 to obtain composite particles. 50 The particle size of the composite particles was 5.5 μm. Then, 40 g of the composite particles and 15 g of Li2S-P2S5-LiCl particles (sulfide-based solid electrolyte, average particle size: 3.0 μm) were placed in a dry mixing device, and the temperature was adjusted to 50 ° C and the speed was adjusted to 2000 rpm. The mixing process was carried out for 5 minutes to obtain the positive electrode active material. The positive electrode active material, Li2S-P2S5-LiCl particles, vapor-grown carbon fiber (VGCF), and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 80:17:2:1 to obtain the positive electrode.

[0075] All-solid-state lithium-ion battery:

[0076] First, a compact of Li2S-P2S5-LiCl particles was formed. Next, a positive electrode was placed on one surface of the compact, and a negative electrode of each embodiment and comparative example was placed on the other surface and they were placed at 6t / cm 2 The laminate was then flattened for 1 minute under a pressing pressure of . Thus, a laminate was obtained. In the laminate obtained at this time, the thickness of the positive electrode and the thickness of the negative electrode were each 130 μm, and the thickness of the separator layer formed by Li2S-P2S5-LiCl was 20 μm. By constraining the laminate under a pressure of 0.2N in the stacking direction, an all-solid-state lithium-ion battery corresponding to each embodiment and comparative example was obtained.

[0077] At 25°C, the all-solid-state lithium-ion batteries corresponding to the embodiments and comparative examples were charged to 4.3V at a constant current of 1C (i.e., the current value at which the theoretical capacity is completely discharged within 1 hour), then charged to a current of 0.05C at a constant voltage, left to stand for 5 minutes, and then discharged to 2.8V at a constant current of 1C, and the actual capacity was recorded as C0.

[0078] Rate performance: Charge the battery to 4.3V at 0.5C0, 1C0, 1.5C0, 2C0, 2.5C0, 3C0, 3.5C0, 4C0, and 4.5C0. After each charge, discharge it to 2.8V at 1C0. Record the charge and discharge performance curves at different charge rates. The higher the capacity, the better the rate performance of the corresponding battery. In the above data, the capacity of the battery at the 50th cycle is used as the result for comparison.

[0079] Cycle performance: The assembled battery is activated at 0.2C0 for one cycle (i.e., one charge and one discharge), and then the cycle performance test is performed at a fixed rate of 0.5C0, with a 5-minute interval between charge and discharge. Under the premise that the battery capacity is maintained at 80% of the first cycle, the more cycles, the better the rate performance of the corresponding battery.

[0080] Table 1 Performance results of all-solid-state lithium-ion batteries corresponding to various embodiments and comparative examples

[0081]

[0082]

[0083] As shown in Table 1, the all-solid-state lithium-ion batteries corresponding to Examples 1 to 3 all achieved higher rate performance and cycle performance, and since Examples 2 and 3 respectively used indium and tin to coat phosphorus, their rate performance and cycle performance were further improved compared with Example 1. However, since Comparative Example 1 used graphite particles as the negative electrode active material, the rate performance and cycle performance of the battery prepared therefrom were worse than those of Example 1 using phosphorus as the negative electrode active material. In Comparative Examples 2 and 3, increasing or decreasing the particle size of phosphorus, respectively, would reduce the battery performance. In Comparative Examples 4 and 5, increasing or decreasing the ratio of the negative electrode active material to the sulfide solid electrolyte, respectively, would also reduce the battery performance.

[0084] like Figure 1 It can be seen that at the microscopic scale, the relative morphology of the sulfide solid electrolyte and the negative electrode active material in Example 2. The sulfide solid electrolyte shown in the figure forms a dense coating layer around the negative electrode active material. It is proved that the present invention can obtain better electrochemical performance, which is inseparable from the dense coating morphology of the sulfide solid electrolyte on the negative electrode active material. Increasing or decreasing the particle size of phosphorus, increasing or decreasing the ratio of the negative electrode active material to the sulfide solid electrolyte, will affect the microscopic relative morphology of the electrolyte and the active material, and then affect the performance of the corresponding all-solid-state lithium-ion battery.

[0085] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution obtained by any modification, equivalent replacement, improvement, etc. made by a person skilled in the art based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art shall be within the scope of protection determined by the claims.

Claims

1. A phosphorus negative electrode, characterized in that: It includes a negative electrode active material and a sulfide solid electrolyte; The sulfide solid electrolyte coats the negative electrode active material; The negative electrode active material includes phosphorus; The phosphorus D 50 20~30μm.

2. The phosphorus negative electrode according to claim 1, characterized in that The negative electrode active material also includes a metal material; the metal material covers the phosphorus.

3. The phosphorus negative electrode according to claim 2, characterized in that: The metal material includes at least one of indium, tin and antimony.

4. The phosphorus negative electrode according to claim 1, characterized in that The D of the sulfide solid electrolyte 50 0.1~5μm.

5. The phosphorus negative electrode according to claim 1, characterized in that: The proportion of the sulfide solid electrolyte covering the surface of the negative electrode active material is 65-100%.

6. The phosphorus negative electrode according to claim 1, characterized in that The mass ratio of the sulfide solid electrolyte to the negative electrode active material is 1:2-3.

7. The method for preparing a phosphorus negative electrode according to any one of claims 1 to 6, characterized in that: The following steps are involved: After phosphorus is pretreated with trace materials, negative electrode active materials are obtained, and then sulfide solid electrolyte is added to perform ball milling mixing, ultrasonic dispersion, heating, and mixing to obtain a phosphorus negative electrode.

8. The preparation method according to claim 7, characterized in that: The following steps are also included: The negative electrode active material is coated with a metal material.

9. The preparation method according to claim 7, characterized in that: The mixing temperature is 45-55° C. and the mixing time is 1-10 min.

10. An all-solid-state lithium-ion battery, characterized in that: The all-solid-state lithium-ion battery comprises the phosphorus negative electrode according to any one of claims 1 to 6.

Citation Information

Cited By

  • Phosphorus-based negative electrode material and preparation method and application thereof

    CN120674484A